2019
DOI: 10.1097/md.0000000000017740
|View full text |Cite
|
Sign up to set email alerts
|

Hospital length of stay following first-time elective open posterior lumbar fusion in elderly patients: a retrospective analysis of the associated clinical factors

Abstract: To identify independent factors associated with prolonged hospital length of stay (LOS) in elderly patients undergoing first-time elective open posterior lumbar fusion surgery. We retrospectively analyzed the data of 303 elderly patients (age range: 60–86 years) who underwent first-time elective open lumbar posterior fusion surgery at our center from December 2012 to December 2017. Preoperative and perioperative variables were extracted and analyzed for all patients, and multivariate stepwise regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, this cutoff was chosen a priori. Other studies have variably defined prolonged hospitalization as admissions lasting more than seven days [ 19 , 23 , 29 , 37 , 38 ] or above the 75th centile for length of stay [ 11 , 12 , 14 , 15 , 17 , 20 , 26 , 27 , 30 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue disruption during surgical procedures and trauma leads to bleeding that interferes with visualization of the surgical area and blood loss that may require replacement with blood or blood products. Trauma-induced hemorrhagic shock is a major cause of morbidity and mortality [33], and bleeding-related complications resulting from surgeries and endovascular interventions has been linked to longer length of hospital stays and higher cost of care for a variety of surgical procedures including neurological, vascular, solid organ, thoracic, cardiac, digestive and reproductive organs, and knee/hip replacements [8,[34][35][36][37][38][39]. Pre-hospitalization and inpatient management of bleeding during surgical procedures is crucial to prevent nonfatal and potentially lifethreatening complications [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The thicker the edge, the more co‐occurrences of the two connected complications. Five studies were excluded from co‐occurrence network analysis because individual postoperative medical complications were not reported (Baker et al, 2017; Drazin et al, 2017; Passias et al, 2017; Sharma et al, 2019; Zhan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%